CRSCA booklet 2012 - University of Wisconsin-River Falls. Chalmer Davee Library (University of Wisconsin-River Falls. Chalmer Davee Library., 2013)
Booklet listing the articles, books, academic posters, fine and performance art, playbills and other items produced by the faculty and staff at the University of Wisconsin-River Falls during the 2012 calendar year.
59 p.
Keywords: Chalmer Davee Library; CRSCA; University of Wisconsin-River Falls--Faculty--Research; University of Wisconsin-River Falls; University of Wisconsin-River Falls--Employees--Research; University of Wisconsin-River Falls--Faculty; University of Wisconsin-River Falls--Employees; University of Wisconsin-River Falls--Research; Celebrating research, scholarship and creative achivement; CRSCA booklet; Universities and colleges--Wisconsin--River Falls--Faculty; University of Wisconsin-River Falls. Chalmer Davee Library; Universities and colleges--Research--Wisconsin--River Falls; Universities and colleges--Wisconsin--River Falls--Employees